Effect of organic additive on the growth and characterization of potassium hydrogen phthalate crystals: third-order nonlinear optical properties. (2021) - Balakrishnan, C.; Manonmani, M.; Vinitha, G.; Meenakshisundaram, S.P.; Sockalingam, R.M.
Abstract: Potassium hydrogen phthalate (KHP) single crystals were grown in the presence of an organic additive, 1, 5-diaminonaphthalene. The effect of the additive on surface morphology and optical properties has been studied. The sharp prominent peaks in the indexed powder X-ray diffraction (PXRD) pattern confirm the crystallinity of the sample and comparison with XRD pattern of pure reveals the stress on KHP structure and it is further supported by minor shifts in IR frequencies. Scanning electron microscope investigation reveals surface morphological changes. Third-order nonlinear optical (NLO) properties of the KHP crystals grown from alcoholic solution containing 1, 5-diaminonaphthalene were derived by employing a single beam Z-scan technique at a wavelength of 532 nm with He-Ne Laser system.